Synthesis and Characterization of Tris(bidentate) Ruthenium Complexes of Di(pyrid‐2‐yl)(methyl)amine. Issue 24 (27th June 2017) - Wu, Si‐Hai; Shao, Jiang‐Yang; Dai, Xiaojuan; Cui, Xiuling; Su, Hongmei; Zhong, Yu‐Wu
Abstract : Three tris(bidentate) monoruthenium complexes [Ru(dpma)(bpy)2 ](PF6 )2 [1 (PF6 )2 ; dpma = di(pyrid‐2‐yl)(methyl)amine, bpy = 2, 2′‐bipyridine], [Ru(dpma)2 (bpy)](PF6 )2 [2 (PF6 )2 ], and [Ru(dpma)3 ](PF6 )2 [3 (PF6 )2 ] with the electron‐rich ligand dpma were synthesized and characterized. The single‐crystal X‐ray structures of1 (PF6 )2 to3 (PF6 )2 are presented. The electrochemical and spectroscopic properties of these complexes were examined and compared with those of the reference complex [Ru(bpy)3 ](PF6 )2 . Complexes1 (PF6 )2 to3 (PF6 )2 show a decreased Ru III/II redox potential by 140–310 mV with respect to [Ru(bpy)3 ](PF6 )2 . The strong emission property of [Ru(bpy)3 ](PF6 )2 is maintained in1 (PF6 )2 and2 (PF6 )2 . However, complex3 (PF6 )2 is only weakly emissive at room temperature. In addition, density functional theory (DFT) and time‐dependent DFT calculations were performed to complement these experimental results. Abstract : Ruthenium complexes containing one, two, or three di(pyrid‐2‐yl)(methyl)amine ligands have been prepared. The electrochemical and photophysical properties of these complexes were examined and compared with those of [Ru(bpy)3 ](PF6 )2 (bpy = 2, 2′‐bipyridine).